The Effect of the Scramble Game-Type Cooperative Learning Model Assisted by Canva Media on Second-Grade Elementary School Students’ Learning Outcomes - Taufiq, Azzahra Rahita; Setyawan, Agung (Universitas Trunojoyo Madura, 2025)
This study aims to determine the influence of the Scramble Game type of cooperative learning model assisted by Canva media on the Indonesian language learning outcomes of second-grade students at SDN Barurambat Kota 1 Pamekasan. The background of this research is based on the low student learning outcomes in Indonesian, caused by a lack of active student involvement and the continued use of teacher-centered learning models. This study employed a quasi-experimental design with a Nonequivalent Control Group Design. The research sample consisted of 56 students, divided into an experimental class and a control class, each comprising 28 students, selected through random sampling. The research instrument was a learning outcome test administered before (pretest) and after (posttest) the treatment. The results showed a significant difference between the posttest scores of students in the experimental and control classes. This was evidenced by a t-test significance value of 0.00 0.05. The mean score difference between the two classes indicated that the experimental class experienced an improvement of 26.536 points higher than the control class. Thus, it can be concluded that the Scramble Game type of cooperative learning model assisted by Canva media has a significant influence on improving the Indonesian language learning outcomes of second-grade students at SDN Barurambat Kota 1 Pamekasan.